Sistema para depleção de proteínas em Xanthomonas citri subsp. citri - Lacerda, Lilian Amaral [UNESP] (2015)
Xanthomonas citri ssp. citri (Xac) is the causal agent of citrus canker, one of the most severe diseases that affect citrus plants of commercial importance around the world. An effective control for citrus canker constitutes the elimination of infected plants in rigorous programs to contain the spread of the bacteria. However, recent relaxation in the policies to combat citrus canker in areas such as the state of São Paulo, Brazil, the major orange juice producer in the world, are contributing to the spread of the disease. Therefore, knowledge of the biology of this plant pathogen and also of the mechanisms involved in plant-pathogen interaction are of great importance to support the development of strategies to deal with citrus canker. Recent work from our group demonstrated that X. citri mutants disrupted for parB are compromised in chromosome segregation and are unable to produce disease symptoms in plant. In the present work, we extended our characterizations by evaluating the effects of a lack of ParB in X. citri mutants carrying a clean deletion of its coding DNA. ParB is a DNA binding protein and is involved in chromosome segregation process through interaction with other proteins. Because of difficult in genes deletion involved this process in X. citri, the parB gene was deleted in a X. citri variant harboring a replicative plasmid able to express extra copies of ParB (ParB-TAP) under the control of the para (arabinose promoter). The viability of the X. citri parB knockout was assessed in growth curve experiments and compared with the wild type strain under different conditions of parB-tap repression or induction. The aim was to explore the conditions depletion and overexpression of ParB and its effects through the characterization of para in X. citri Thus, the X. citri parB knockout was visualized under differential interference contrast (DIC) microscopy in order to detect morphological alterations normally expected from ...